Efficient one-pot lactic acid production from cellulose via a Trichoderma reesei and Bacillus coagulans cooperation leveraging substrate-induced secretomes - Shuai Liang; Chang Yu; Jiaming Fu; Yuanming Tao; Zhaojuan Zheng; Jia Ouyang (Bioresource Technology, 2026)

Nickel from olivine dissolution induces diel photodamage and metabolic adjustment in Gracilariopsis lemaneiformis - Chang Liu; Dong Xu; Xuewei Wang; Yiqun Wu; Yuan Chang; Jiaming Zhang; Xinyu Qian; Ling Liu; Ping Li; Zhi-Hua Li (Journal of Hazardous Materials, 2026)

High-accuracy estimation of global site-level soil heterotrophic respiration through Geo-XGBoost integration with expanded datasets and remote sensing - Jie Liu; Ni Huang; Luying Zhu; Jiaming Chang; Yuting Shi; Zheng Niu; Dewen Cai; Li Wang (Agricultural and Forest Meteorology, 2026)

Molecularly functionalized high-Q THz metasurface via q-BIC for selective HbA1c detection - Chang Liu; Min Gao; Zichen Zhang; Junxiao Liu; Ligeng Jin; Xin Tian; Lijun Jiang; Zhongmei Zheng; Chuanyue Li; Jiaming Feng; Xingyu Liao; Zhihang Long; et al. (Chemical Engineering Journal, 2026)

Morphology–aware spatiotemporal prediction of cumulonimbus–related radar echoes using CSDP–Net - Deyi Wang; Xu Wang; Zhenhong Cheng; Xin Chang; Hongping Yuan; Jixiang Yang; Yi Liang; Jiaming Hu; Ting Zhang (Theoretical and Applied Climatology, 2026)

Investigation of CO2 absorption and desorption performance and mechanism of aqueous [TETAH][Im] in a PTFE hollow fiber membrane contactor - Chunyun Zhou; Yanbin Yun; Chang Li; Jia Liu; Jiaming Mao; Wenjuan Yang; Haiyan Huang; Guoqiang Zhuang; Meng Li (Journal of Environmental Chemical Engineering, 2026)

Efficacy and Safety of OnabotulinumtoxinA for the Treatment of Masseter Muscle Prominence in a Chinese Population: 6-Month Results From a Phase 3, Randomized, Placebo-Controlled Study - Jiaming Sun; Yuejun Li; Tianjiao Yang; Jia Chang (Toxicon, 2026)

Monthly Soil Respiration in China's Forests: Spatiotemporal Patterns and Drivers Over 21 Years - Jiaming Chang; Ni Huang; Li Wang; Luying Zhu; Xiaoyu Lin; Jie Liu; Zheng Niu; Dewen Cai (Global Change Biology, 2026)
Forests play a critical role as terrestrial carbon sinks in mitigating climate change. However, accurate quantification of soil respiration ( R s )—the primary CO 2 efflux from forests—remains challenging due to existing studies' overreliance on annual‐scale estimates, which obscure fine‐scale spatiotemporal dynamics and key drivers of R s . Here, we developed a 500 m resolution monthly R s dataset for China's forests (2000–2020) using remote sensing data and a geographically weighted machine learning model. A geographically weighted extreme gradient boosting model achieved the highest accuracy in predicting monthly R s ( R 2 = 0.74, RMSE = 0.8 g C m −2 day −1 ). The mean total annual R s from 2000 to 2020 was 2.32 ± 0.09 Pg C year −1 , with summer contributing most and winter least. Annual total R s and seasonal total R s showed significant increasing trends across China's forests from 2000 to 2020, with the strongest increases in southern China's young/middle‐aged natural management forests and plantations. The relationships between R s and its driving factors varied: gross primary productivity (GPP) was the primary driver of annual R s across all forest management and age classes. Seasonally, temperature dominated R s in spring/winter, and GPP dominated summer R s across all forest management and age classes, while precipitation effects varied with management/age classes and season. Our findings highlight the necessity of monthly‐scale analysis and the significant role of forest management and age in modulating R s variability.

Construction of biochar-zeolite composite for enhanced VOCs adsorption: Interfacial reinforcement and steam-driven synergistic regulation of pore formation and dealumination - Dingcheng Liang; Yajie Chang; Peipei Zhang; Yuan Liu; Chenhong Luo; Zhijun Zhang; Qiang Xie; Jiaming Liang; Kangzhou Wang; Xiao Yang; Qingping Chen; Zhucan Xie; et al. (Journal of Cleaner Production, 2025)

Role of adiabatic heating in winter warming over the Tibetan Plateau - Jiaming Tan; Meiyu Chang; Zouxing Lin; Zhiyan Zuo (Science China Earth Sciences, 2025)

Enhanced carbon dioxide capture via amphiphobic PVDF membrane modification for membrane contactors: Overcoming wettability challenges - Chang Li; Yanbin Yun; Fengguang Huang; Jiaming Mao; Jia Liu; Wenjuan Yang; Chunyun Zhou; Meng Li (Chemical Engineering Journal, 2025)

Anhydrous deep eutectic solvents-based biphasic absorbents for efficient CO2 capture: Unravelling the critical role of hydrogen bond-mediated electron transfer - Jiaming Mao; Yunqian Ma; Yuhui Ci; Jia Liu; Chang Li; Wenjuan Yang; Chunyun Zhou; Hongwei Xie; Yanbin Yun (Chemical Engineering Journal, 2025)

A NH2-UiO-66-TiO2/Al2O3 hollow ceramic membrane with an enhanced photocatalytic oxidation performance of NO - Wenjuan Yang; Wenli Liu; Yuanbo Song; Yangyang Wang; Yanbin Yun; Guicheng Liu; Chang Li; Jiaming Mao; Jia Liu; Meng Li; Chunyun Zhou; Manxiang Wang; et al. (Journal of Environmental Chemical Engineering, 2025)

Experimental and theoretical investigation of an ionic liquid-based biphasic solvent for post-combustion CO2 Capture: Breaking through the “Trade-off” effect of viscosity and loading - Jiaming Mao; Yuhui Ci; Jia Liu; Chang Li; Wenjuan Yang; Yanbin Yun; Guicheng Liu; Meng Li; Manxiang Wang (Chemical Engineering Journal, 2024)

Biochar reduces gaseous emissions during poultry manure composting: Evidence from the evolution of associated functional genes - Ruijing Dang; Yu Cai; Jiaming Li; Yilin Kong; Tao Jiang; Jiali Chang; Sheng Yao; Jing Yuan; Guoxue Li; Guoying Wang (Journal of Cleaner Production, 2024)

Biphasic solvents based on dual-functionalized ionic liquid for enhanced post-combustion CO2 capture and corrosion inhibition during the absorption process - Jiaming Mao; Chang Li; Yanbin Yun; Jia Liu; Wenjuan Yang; Meng Li; Lihua Wang; Chunli Li; Wenli Liu (Chemical Engineering Journal, 2024)

Rapid adaptive evolution of Bacillus coagulans to undetoxified corncob hydrolysates for lactic acid production and new insights into its high phenolic degradation - Jiaming Fu; Zijie Wang; Hongcheng Miao; Chang Yu; Zhaojuan Zheng; Jia Ouyang (Bioresource Technology, 2023)

Performance and response of coupled microbial fuel cells for enhanced anaerobic treatment of azo dye wastewater with simultaneous recovery of electrical energy - Liming Hu; Na Liu; Chang Li; Jiaming Mao; Meng Li; Yanbin Yun; Wenli Liu (Environmental Science and Pollution Research, 2023)

Self-powered health monitoring with ultrafast response and recovery enabled by nanostructured silicon moisture-electric generator - Yuhang Song; Chang Shu; Zheheng Song; Xuelian Zeng; Xianrong Yuan; Yanan Wang; Jiaming Xu; Qianyue Feng; Tao Song; Beibei Shao; Yusheng Wang; Baoquan Sun (Chemical Engineering Journal, 2023)

From remotely‐sensed solar‐induced chlorophyll fluorescence to ecosystem structure, function, and service: Part II—Harnessing data - Ying Sun; Jiaming Wen; Lianhong Gu; Joanna Joiner; Christine Y. Chang; Christiaan van der Tol; Albert Porcar‐Castell; Troy Magney; Lixin Wang; Leiqiu Hu; Uwe Rascher; Pablo Zarco‐Tejada; et al. (Global Change Biology, 2023)
Although our observing capabilities of solar‐induced chlorophyll fluorescence (SIF) have been growing rapidly, the quality and consistency of SIF datasets are still in an active stage of research and development. As a result, there are considerable inconsistencies among diverse SIF datasets at all scales and the widespread applications of them have led to contradictory findings. The present review is the second of the two companion reviews, and data oriented. It aims to (1) synthesize the variety, scale, and uncertainty of existing SIF datasets, (2) synthesize the diverse applications in the sector of ecology, agriculture, hydrology, climate, and socioeconomics, and (3) clarify how such data inconsistency superimposed with the theoretical complexities laid out in (Sun et al., 2023) may impact process interpretation of various applications and contribute to inconsistent findings. We emphasize that accurate interpretation of the functional relationships between SIF and other ecological indicators is contingent upon complete understanding of SIF data quality and uncertainty. Biases and uncertainties in SIF observations can significantly confound interpretation of their relationships and how such relationships respond to environmental variations. Built upon our syntheses, we summarize existing gaps and uncertainties in current SIF observations. Further, we offer our perspectives on innovations needed to help improve informing ecosystem structure, function, and service under climate change, including enhancing in‐situ SIF observing capability especially in “data desert” regions, improving cross‐instrument data standardization and network coordination, and advancing applications by fully harnessing theory and data.

From remotely sensed solar‐induced chlorophyll fluorescence to ecosystem structure, function, and service: Part I—Harnessing theory - Ying Sun; Lianhong Gu; Jiaming Wen; Christiaan van der Tol; Albert Porcar‐Castell; Joanna Joiner; Christine Y. Chang; Troy Magney; Lixin Wang; Leiqiu Hu; Uwe Rascher; Pablo Zarco‐Tejada; et al. (Global Change Biology, 2023)
Solar‐induced chlorophyll fluorescence (SIF) is a remotely sensed optical signal emitted during the light reactions of photosynthesis. The past two decades have witnessed an explosion in availability of SIF data at increasingly higher spatial and temporal resolutions, sparking applications in diverse research sectors (e.g., ecology, agriculture, hydrology, climate, and socioeconomics). These applications must deal with complexities caused by tremendous variations in scale and the impacts of interacting and superimposing plant physiology and three‐dimensional vegetation structure on the emission and scattering of SIF. At present, these complexities have not been overcome. To advance future research, the two companion reviews aim to (1) develop an analytical framework for inferring terrestrial vegetation structures and function that are tied to SIF emission, (2) synthesize progress and identify challenges in SIF research via the lens of multi‐sector applications, and (3) map out actionable solutions to tackle these challenges and offer our vision for research priorities over the next 5–10 years based on the proposed analytical framework. This paper is the first of the two companion reviews, and theory oriented. It introduces a theoretically rigorous yet practically applicable analytical framework. Guided by this framework, we offer theoretical perspectives on three overarching questions: (1) The forward (mechanism) question —How are the dynamics of SIF affected by terrestrial ecosystem structure and function? (2) The inference question : What aspects of terrestrial ecosystem structure, function, and service can be reliably inferred from remotely sensed SIF and how? (3) The innovation question : What innovations are needed to realize the full potential of SIF remote sensing for real‐world applications under climate change? The analytical framework elucidates that process complexity must be appreciated in inferring ecosystem structure and function from the observed SIF; this framework can serve as a diagnosis and inference tool for versatile applications across diverse spatial and temporal scales.

Biomarkers of aging - Hainan Bao; Jiani Cao; Mengting Chen; Min Chen; Wei Chen; Xiao Chen; Yanhao Chen; Yu Chen; Yutian Chen; Zhiyang Chen; Jagadish K. Chhetri; Yingjie Ding; et al. (Science China Life Sciences, 2023)

Chemical constituents from the leaves of psidium guajava linn. and their chemotaxonomic significance - Guangxin Zhou; Jiaming Zhao; Chang Gong; Jixuan Xu; Ce Song; Dali Meng (Natural Product Research, 2023)

A sustainable development pattern integrating data centers and pasture-based agrivoltaic systems for ecologically fragile areas - Jiaming Zhang; Tao Wang; Yuan Chang; Bingsheng Liu (Resources, Conservation and Recycling, 2023)

TP-DDI: A Two-Pathway Deep Neural Network for Drug–Drug Interaction Prediction - Jiang Xie; Chang Zhao; Jiaming Ouyang; Hongjian He; Dingkai Huang; Mengjiao Liu; Jiao Wang; Wenjun Zhang (Interdisciplinary Sciences: Computational Life Sciences, 2022)

A Highly Sensitive Solid Substrate Room Temperature Phosphorimetry for Carbaryl Detection Based on its Activating Effect on NaIO4 Oxidizing Fluorescein - Jiaming Liu; Qitong Huang; Zhen-bo Liu; Xiaofeng Lin; Li-Hong Zhang; Chang-Qing Lin; Zhi-Yong Zheng (Journal of Fluorescence, 2014)

Highly Sensitive Fluorescent Probe for Clenbuterol Hydrochloride Detection Based on its Catalytic Oxidation of Eosine Y by NaIO4 - Jiaming Liu; Zhen-bo Liu; Qitong Huang; Chang-Qing Lin; Xiaofeng Lin (Journal of Fluorescence, 2014)